Evaluating the Legality of GI Airline Standard Terms Through Contract Anatomy and Consumer Protection Frameworks - Clarissa Gunawan; Kendrapatya Grisha Sashenka; Nur Dwi Andhika Putra; Nazara Anisa Nurrahma; Mochamad Daffa Khaedar Ali; Dwi Aryanti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the contract between GI as an airline service provider and consumers based on contract anatomy and applicable legal foundations. The analysis focuses on the conformity of the contract's content with contract law principles, the rights and obligations of the parties involved, and consumer protection. The results indicate that the contract clearly stipulates rights and obligations, yet certain legal aspects need to be strengthened to optimally safeguard consumer interests